Predictors of CMV Infection in CMV-Seropositive Kidney Transplant Recipients: Impact of Pretransplant CMV-Specific Humoral Immunity - Similan Kirisri (2022)
Background: Although cytomegalovirus (CMV)-seropositive solid organ transplant recipients have a relatively lower risk of CMV infection than CMV-seronegative recipients who receive allograft from CMV-seropositive donors, some patients remain at risk of CMV infection after transplant. We investigated the pretransplant CMV-specific humoral immunity (CHI) and other CMV infection predictors in CMV-seropositive kidney transplant (KT) recipients. Methods: This retrospective study was conducted on adult CMV-seropositive KT recipients during 2017 and 2018. The cumulative incidence of CMV infection was estimated using the Kaplan-Meier method. CHI, measured with an enzyme-linked fluorescent immunoassay and other predictors for CMV infection, was analyzed using Cox proportional hazards models. Results: Of the 340 CMV-seropositive KT recipients (37% female; mean ± SD age, 43 ± 11 years), 69% received deceased-donor allograft and 64% received induction therapy. During a mean follow-up of 14 months, the cumulative incidence of CMV infection was 14.8%. In multivariate analysis, low pretransplant CHI (defined as anti-CMV immunoglobulin [IgG] titer <20 AU/mL) was significantly associated with CMV infection (hazard ratio [HR], 2.98; 95% CI, 1.31-6.77; P =.009). Other significant predictors of CMV infection included older donor age (HR, 1.03; 95% CI, 1.01-1.06; P =.005), antithymocyte induction therapy (HR, 2.90; 95% CI, 1.09-7.74; P =.033), and prolonged cold ischemic time (HR, 1.06; 95% CI, 1.02-1.10; P =.002). Conclusions: A low pretransplant CHI is independently associated with post-transplant CMV infection in CMV-seropositive KT recipients. A quantitative anti-CMV IgG assay could potentially stratify CMV-seropositive patients at risk of CMV infection after KT.